(3aJM GdbQjH GdeLjH Ydi GdJQZjH hGdJQgjHs - (3MSf Hf YdjGdajhej GdbGgQj, CHh Ydj,J (B870 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA cJGH GdLfGFR Hbhdg (B: (3Udi Gddg Ydjg hSde hQLd NGa Ydi faSg GdYfJ aJYaa HfcGM EeQCI GdMOjK s
(3BNQgG (B:s
(3jfJgi GdehLhO efg (B: (3HGdJZQjH ai GdHchQ ai WdH GdQRb hZjQg Hbhdg (B: (3hai MOjK BNQ Yf CHj gQjQI bGd bGd QShd Gddg Udi Gddg Ydjg hSde HhQc dCeJi ai HchQgG jhe NejSgG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jhLO HGdLRA HjGV bdjds
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs